An overview of ischemic preconditioning in exercise performance: A systematic review - Maxime Caru; Ariane Levesque; François Lalonde; Daniel Curnier (Elsevier, 2019)
Ischemic preconditioning (IPC) is an attractive method for athletes owing to its potential to enhance exercise performance. However, the effectiveness of the IPC intervention in the field of sports science remains mitigated. The number of cycles of ischemia and reperfusion, as well as the duration of the cycle, varies from one study to another. Thus, the aim of this systematic review was to provide a comprehensive review examining the IPC literature in sports science. A systematic literature search was performed in PubMed (MEDLINE) (from 1946 to May 2018), Web of Science (sport sciences) (from 1945 to May 2018), and EMBASE (from 1974 to May 2018). We included all studies investigating the effects of IPC on exercise performance in human subjects. To assess scientific evidence for each study, this review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. The electronic database search generated 441 potential articles that were screened for eligibility. A total of 52 studies were identified as eligible and valid for this systematic review. The studies included were of high quality, with 48 of the 52 studies having a randomized, controlled trial design. Most studied showed that IPC intervention can be beneficial to exercise performance. However, IPC intervention seems to be more beneficial to healthy subjects who wish to enhance their performance in aerobic exercises than athletes. Thus, this systematic review highlights that a better knowledge of the mechanisms generated by the IPC intervention would make it possible to optimize the protocols according to the characteristics of the subjects with the aim of suggesting to the subjects the best possible experience of IPC intervention. Keywords: Exercise, Human performance, IPC protocols, Ischemic preconditioning, Sports science